2022
DOI: 10.1007/s00423-022-02531-7
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Fistula and Biochemical Leak after Splenectomy: Incidence and Risk Factors—A Retrospective Single-Center Analysis

Abstract: Purpose Postoperative pancreatic fistula (POPF) is a complication discussed in the context of pancreatic surgery, but may also result from splenectomy; a relationship that has not been investigated extensively yet. Methods This retrospective single-center study aimed to analyze incidence of and risk factors for POPF after splenectomy. Patient characteristics included demographic data, surgical procedure, and intra- and postoperative complications. POPF was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…When excluding BL to focus entirely on grade B and grade C fistula, we found an incidence of 5.1%, which is comparable to rates reported in the literature [2,[5][6][7]17].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…When excluding BL to focus entirely on grade B and grade C fistula, we found an incidence of 5.1%, which is comparable to rates reported in the literature [2,[5][6][7]17].…”
Section: Discussionsupporting
confidence: 85%
“…Although splenectomy remains a frequently performed procedure, studies on pancreatic complications after splenectomy are limited. Especially, the incidence of POPF after isolated splenectomy and the effects of pancreatic fistula on short-term clinical outcomes is unclear [2,[5][6][7]. This single-center retrospective study showed that pancreatic leak is not a rare complication and occurs in 23.7% of patients difficulties during the course of other surgical procedures [5].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations